The Inferred Formation of a Subice Platelet Layer Below the Multiyear Landfast Sea Ice in the Wandel Sea (NE Greenland) Induced by Meltwater Drainage. Issue 5 (17th May 2018) - Kirillov, S.; Dmitrenko, I.; Rysgaard, S.; Babb, D.; Ehn, J.; Bendtsen, J.; Boone, W.; Barber, D.; Geilfus, N.
Abstract: Oceanographic and ice‐mass‐balance records are presented from two moorings deployed on landfast multiyear ice in the Wandel Sea (North Greenland) during June–August 2015. Here we show that the melting and drainage of >1 m of snow from June 14 to July 14 created a double‐diffusive vertical stratification which resulted in supercooling of water and enabled the formation of platelet crystals below the sea ice. Although the effect of supercooling, with temperatures up to 0.5°C below the freezing point, might be overestimated considerably in our records, this process led to the formation of ∼1.1–1.2 m‐thick subice platelet layer. While warm water temperatures lead to the complete loss of this layer at one mooring site, the layer persisted through summer and became incorporated into the congelation ice at the second site. The warm water that melted out the platelet layer can be ascribed to two different sources: (1) in situ heating from solar radiation resulting in a temperature increase up to 0.8°C in late July and (2) advection of warm surface water (with temperatures up to 3–4°C) from the ice‐free coastal regions in mid‐August. The combination of processes causing the seasonal growth of a platelet layer and either its subsequent ablation or incorporation into congelation ice is discussed with respect to the ice‐mass balance and stability of the landfast ice cover in the Wandel Sea. Furthermore, this study provides evidence for the formation of a platelet layer in the Arctic, a phenomenon that historically has only been observed in the Antarctic. Key Points: Snow depths greater than 1.5 m on the landfast sea ice in the Wandel Sea lead to considerable freshening of the surface layer during summer Ice formation at the subice density interface results in the formation of a 1.1–1.2 m subice platelet layer The platelet layer may persist through the summer and become incorporated into congelation ice, though these processes may vary spatially